Double Anonymity and the Peer Review Process - Richard J.C. Brown (The Scientific World Journal)
The process of peer review for submissions to scientific journals is a well-established and widely used procedure. Review by one's peers is a well-recognised and long-standing method of appraisal. Throughout all branches of science, medicine, humanities, art, literature, politics, sport, and in fact almost all areas of human endeavour, the judgement of work by an individual or group of experts in similar fields of study is the most rigorous and valuable form of recognition. “Peer review”, as this process is commonly known, is an important method of assuring quality, relevance and novelty of work. However, is there still room for improvement in the procedural aspects of peer review?